Evaluation on effect of abrasive blasting media to the environment and human safety and health - Zakaria, Hanis; Hassan, Suhaimi; Azmi, Mohd Azham (Penerbit UTHM, 2020)
Abrasive blasting is one of the methods available for cleaning and finishing for materials using abrasive media towards the workpiece. These include surface cleaning of steels, bricks and concrete. This method is favorable due to fast process and high quality for coating process which increase its efficiency and productivity. However, sand blasting produces significant noise and vibrations, and an effluent cloud consisting of dust, waste sands and contaminants which considered safety risks to on-site personnel and hazardous to surrounding environment. Also, the abrasive blasting requires high working pressure for blasting and be conducted in a controlled working space environment. Since the sand blasting particles are small, and the failure of some workers to abide tight regulation, has made the workers prone to health and safety problems. This research aims to evaluate the effect of abrasive blasting and its processes towards the environment and also human's health and safety. This research is divided into three main areas. The first method assess the process of sand blasting. Some industries are evaluated for chemical hazard risk assessment, of which will be compared with the guidelines under Malaysia legislation body. The second approach will analyse the materials used for sand blasting. These include the blasting media and also parts to be blasted. The chemical compositions and geometry before and after blasting processes will be evaluated in respect of human safety and health...